Applicability of 4 localized-calibration methods in underwater motion analysis - Kwon, Y. V.; Lindley, S. (coachesinfo.com, 1999)
Four different localized-calibration methods were developed based on the DLT (direct linear transformation) algorithm in an effort to reduce the error due to refraction in underwater motion analysis. Their applicability in underwater motion analysis was assessed based on a simulated 3D calibration trial with 2 cameras and a hexahedral calibration frame. It was concluded from the analysis of the calibration results that (a) all methods substantially reduced the maximum reconstruction error and demonstrated the potential to minimize object space deformation, (b) localization methods based on overlapped control volumes/areas revealed superior performance than those based on distinct volumes/areas, and (c) the 2D DLT-based localization algorithm provided more accurate object space reconstruction than the 3D DLT-based algorithm.